Polynomial of Degree Four Interpolation on Triangles (Journal of Computational Mathematics, 1991)
A method for constructing the $C^1$ piecewise polynomial surface of degree four on triangles is presented in this paper. On every triangle, only nine interpolation conditions, which are function values and first partial derivatives at the vertices of the triangle, are needed for constructing the surface.